Dysembryoplastic neuroepithelial tumor of the midbrain tectum: A case report - (:unkn) unknown (My University, 2002)
Dysembryoplastic neuroepithelial tumor (DNT) is a relatively new nosologic entity. First described in 1988, it is now included in the "neuronal and mixed neuronal-glial tumours" category in the revised 2000 World Health Organization (WHO) Classification of Tumours of the Nervous System. The collective experience of more than 300 reported cases indicates that, with only rare exceptions, DNTs are cerebral cortical lesions. At present, the actual incidence of extracortical DNT is unknown. We describe, the clinicopathologic features of the first tectal DNT. The patient was a 51-year-old man with a 2-month history of pulsatile headaches. On neurologic examination, the only abnormality was gait ataxia. Magnetic resonance imaging (MRI) demonstrated a midbrain tumor involving the tectum. It was hypointense on T1-weighted images and featured an iso- to hyperintense nodule at its center. The nodule showed enhancement upon contrast administration. No aqueductal obstruction or intraventricular extension of tumor was detected. The tumor was approached supratentorially and removed completely. The mucoid tumor was well demarcated from neural tissue. Histopathologically, it was a typical DNT, exhibiting a nodular pattern of growth with a "specific glioneuronal component". This case report documents the first DNT to arise in the midbrain tectum and focuses on the problem of diagnosing this uncommon tumor at extracortical sites.
Keywords: Dysembryoplastic neuroepithelial tumor (DNT); Extracortical DNT; Midbrain; Neuroimaging; Tectum